FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KELELAHAN KERJA PADA PEKERJA PROYEK PEMBANGUNAN BINTARO XCHANGE TAHAP II PT JAYA KONSTRUKSI MANGGALA PRATAMA, TBK., TAHUN 2023 : Faktor-Faktor yang Berhubungan dengan Tingkat Kelelahan Kerja pada Pekerja Proyek Pembangunan Bintaro Xchange Tahap II PT Jaya Konstruksi Manggala Pratama, Tbk., Tahun 2023 - Shafa Sausan (2023)
Work fatigue is a condition both physical and mental that causes a decrase in the ability of the body's endurance. Work fatigue can have a negative impact on work performance, company production capacity and work accidents. The construction industry is a type of work where workers are prone to work fatigue. This study aims to determine the factors associated with work fatigue in workers at the second stage of Bintaro Xchange construction project. This research is a quantitative research with cross sectional research design. Determination of the sample in this study using total sampling with a total of 85 respondents. This research instrument used the Industrial Fatigue Research Committee (IFRC) questionnaire, the Workplace Stress Scale (WSS) questionnaire, meters and scales which were then analyzed using the Chi-Square test. The results of the univariate analysis showed that 82,4% of workers experienced moderate category of work fatigue. The results of bivariate analysis with chi-square obtained four factors that have a relationship with work fatigue, namely smoke habits (p = 0,022), sleep duration (p = 0,048), work duration (p = 0,019) and work stress (p = 0,033). It is hoped that PT Jaya Contruction can be better deal with hazards related to work fatigue such as increase the number of workers and rearranging the working hour system.